Elucidation of TRIM25 ubiquitination targets involved in diverse cellular and antiviral processes. - Emily Yang; Serina Huang; Yasaman Jami-Alahmadi; Gerald M McInerney; James A Wohlschlegel; Melody M H Li (PLoS Pathogens, 2022)
The tripartite motif (TRIM) family of E3 ubiquitin ligases is well known for its roles in antiviral restriction and innate immunity regulation, in addition to many other cellular pathways. In particular, TRIM25-mediated ubiquitination affects both carcinogenesis and antiviral response. While individual substrates have been identified for TRIM25, it remains unclear how it regulates diverse processes. Here we characterized a mutation, R54P, critical for TRIM25 catalytic activity, which we successfully utilized to "trap" substrates. We demonstrated that TRIM25 targets proteins implicated in stress granule formation (G3BP1/2), nonsense-mediated mRNA decay (UPF1), nucleoside synthesis (NME1), and mRNA translation and stability (PABPC4). The R54P mutation abolishes TRIM25 inhibition of alphaviruses independently of the host interferon response, suggesting that this antiviral effect is a direct consequence of ubiquitination. Consistent with that, we observed diminished antiviral activity upon knockdown of several TRIM25-R54P specific interactors including NME1 and PABPC4. Our findings highlight that multiple substrates mediate the cellular and antiviral activities of TRIM25, illustrating the multi-faceted role of this ubiquitination network in modulating diverse biological processes.